Comparison of web application development using PHP and Magento platforms - Drawdzik, Bartosz; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2018)
The paper presents the process of creating two application using two different methods of programming. One of them is simple PHP application based on data stored in a relational MySQL database and a application of the same functionality implemented on the Magento 1.9 platform. The main purpose of the paper is to test applications and verify them of the extent to which functionality is fault-tolerant. It means that tests will be the - individuals function and their resistance to errors. The obtained results allow the authors to evaluate which kind of programming is the best and improve clean code and it’s quality.